The Fear of God in Early Modern Political Theory - Wootton, David (Historical Papers / Communications historiques, 1983)
Abstract A group's collective identity is a complex phenomenon which is always difficult to delineate and understand, but however one does so, historical antecedents must be a crucial element. This year's "Presidential Address" explores this important question, which was raised in an earlier presidential discourse. On that occasion, Robert Craig Brown noted that "historical knowledge is an essential component of a nation's sense of cultural identity. ' ' Professor Wallot elucidates this theme: without a concept of what you have been, you cannot know who you are, or what you can be. As one of the characters in Joy Kogama's novel Obasan observes, "you are your history. If you cut off any of it, you're an amputee. ' 'Professor Wallot sets out to explore this problem by examining the Lower Canadian identity between roughly 1780 and 1815, in order to place the colony within the context of the culture of the North Atlantic world. Though Quebec/Lower Canada has often been portrayed as a closed society, relatively homogenous in its attitudes, cut off from its intellectual roots, and somewhat unsympathetic to new ideas, study of aspects of its culture suggest otherwise. The colony had access to contemporary international thought, in all of its variety, and was more than a passive observer in the clash of ideas and the rhythms of cultural change then current in Europe. In arriving at these conclusions, the author presents a two-part defence; in the first part of his paper, he examines the means of cultural diffusion, the role of printed materials in the formation of attitudes and the rapidity with which European ideas were transferred to Quebec. He concludes that, when one removes the time required to transmit these ideas, the colony was aware of, and deeply involved in, the intellectual cross-currents of the North Atlantic world.The author then proceeds to test the validity of this point by examining three quite different aspects of public culture: the discussion aroused by the fear of overpopulation and consequent impoverishment; the banking system and money, and finally, parliamentary theory and practice. In each of these fields, Professor Wallot concludes, the colony's cultural élite, at the very least, was aware of, and responsive to, recent European thought. In a society which boasted nearly universal literacy, this conclusion suggests a culture far more up-to-date than previous work would lead us to expect.